Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

3y+45=10y+17 solve for y

Pre-Algebra
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SIGN UP FOR FREE
Use mathway.com
Ok
y=4

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

It gives you the answer
get y by itself by -3y from both sides. Then subtract 17 from both sides, that gives you 7y=28 then divide both sides by 7 and you get 4.
3y+45=10y+17 45-17=10y-3y 28 = 7y y = 28/7 therefore y = 4
well you just go through the numbers for y such as y=1, y=2, y=3 and work out the probem untill you get your answer
FULL EXPLANATION AND ANSWER 3y+45=10y+17 Since 10y contains the variable to solve for, move it to the left-hand side of the equation by subtracting 10y from both sides. 3y+45-10y=17 Since 3y and -10y are like terms, add -10y to 3y to get -7y. -7y+45=17 Since 45 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 45 from both sides. -7y=-45+17 Add 17 to -45 to get -28. -7y=-28 Divide each term in the equation by -7. -(7y)/(-7)=-(28)/(-7) Simplify the left-hand side of the equation by canceling the common factors. y=-(28)/(-7) Simplify the right-hand side of the equation by simplifying each term. y=4

Not the answer you are looking for?

Search for more explanations.

Ask your own question